Pengaruh pendidikan, pantangan makanan, dan citra tubuh pada konsumsi gizi makro ibu nifas - Zahra Lutfiah Safitri; Widati Fatmaningrum; Ivon Diah Wittiarika (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Impact of education, food restriction, and body image on postpartum nutrientBackground: The level of nutritional consumption of postpartum mothers increases for the need for tissue repair and the breastfeeding process, but in practice, there are still many postpartum mothers who have not met the recommended level of nutritional consumption due to several factors, including education level, dietary restriction, and body image. Objective: This research seeks to determine the relationship between education level, dietary restriction culture, and body image with the level of macro nutritional consumption. Method: This research implemented an observational analytic method with a cross-sectional design. The sample size was 40 mothers selected using the convenience sampling technique, with data obtained through face-to-face, Google form, and telephone. The independent variables are education level, dietary restriction culture, and body image. The dependent variable is macro nutritional consumption, including energy, carbohydrates, protein, and fat. The instruments used were the Body Shape Questionnaire (BSQ) to measure body image, the food recall questionnaire, and the food frequency questionnaire (FFQ) to measure nutritional consumption. Data analysis was performed using the Chi-Square test. Results: The results showed that most of the mothers had not met their energy, carbohydrate, and protein needs but were able to consume fat that exceeded the nutritional adequacy rate. The analysis results showed no relationship between education level, dietary restriction culture, and body image with consumption of macronutrients (p>0.05). : There is no relationship between education level, dietary restriction culture, body image with the level of nutritional consumption of energy, carbohydrate, protein, and fat.